Melanoma-Derived Exosomes Induce PD-1 Overexpression and Tumor Progression via Mesenchymal Stem Cell Oncogenic Reprogramming - Gyukity-Sebestyén, Edina; Harmati, Mária; Dobra, Gabriella; Németh, István B.; Mihály, Johanna; Zvara, Ágnes; Hunyadi-Gulyás, Éva; Katona, Róbert; Nagy, István; Horváth, Péter; Bálind, Árpád; Szkalisity, Ábel; et al. (Frontiers in Immunology, 2019)
Recently, it has been described that PD-1 overexpressing melanoma cells are highly aggressive. However, until now it has not been defined which factors lead to the generation of PD-1 overexpressing subpopulations. Here, we present that melanoma-derived exosomes, conveying oncogenic molecular reprogramming, induce the formation of a melanoma-like, PD-1 overexpressing cell population (mMSCPD-1+) from naïve mesenchymal stem cells (MSCs). Exosomes and mMSCPD 1+ cells induce tumor progression and expression of oncogenic factors in vivo. Finally, we revealed a characteristic, tumorigenic signaling network combining the upregulated molecules (e.g., PD-1, MET, RAF1, BCL2, MTOR) and their upstream exosomal regulating proteins and miRNAs. Our study highlights the complexity of exosomal communication during tumor progression and contributes to the detailed understanding of metastatic processes.